Perlindungan Hukum bagi Bank (Kreditur) bila Debitur Kredit Macet dengan Jaminan Hak Cipta - Riandhyka Rahandono; Azizul Hakiki; Achmad Rifqi Nizam (JURNAL RECHTENS, 2019)
One of the economic development forms is the existence of the developed companies in allfields, both services and goods. In order to be able to develop a company in line with theplan and to be successful, it certainly needs capital support (fund) which can be obtainedfrom Banking Institution with a collateral form called Patent Right. This research isjuridical-normative (legal research), that is the research focused on analysing rules ornorms in positive law. The research concludes that Patent Right can be made as the maincollateral of credit agreement because it can be categorized as intangible moving objectwhich has economic value. However, because Patent Right is a new collateral form, it isdifficult to assess its economic value and there is no regulation of it. In practice theBanking Institution has not been able to accept Patent Right as the main collateral, butonly as additional collateral.Key Words : Bank, Collateral, Patent Right